EFFICIENCY OF RECIPROCATING FILES IN REMOVAL OF GUTTACORE AND SINGLE-CONE FROM CURVED ROOT CANALS: A MICRO-CT ANALYSIS - HASSAN , REGIR RAMADHAN; IBRAHIM, ABDULKAREEM RAMADHAN (Journal of Duhok University, 2023)
Aims: The purpose of this study was to assess and compare the retreatment ability of different reciprocating single file systems in curved canals obturated with GuttaCore and single-cone obturation techniques using microcomputed tomography. Methods: Sixty-four mandibular molar teeth with root canal systems that have two independent severely curved canals in the mesial root have been chosen for the current study. The root canals have been instrumented with WaveOne Gold primary file and obturated by two techniques: Group SC filled with Single-cone and group GC filled with GuttaCore obturation techniques, using AH Plus sealer in both methods. First micro-CT scan has been taken and the samples have been subdivided into 4 groups for each obturation technique (n16 canals each) according to the retreatment system: Group R: Reciproc (R25 file), group RB: Reciproc Blue (R25 file), group WO: WaveOne (Primary file 25) and group WOG: WaveOne Gold (Primary file 25). After the retreatment procedures, the second micro-CT scan has been taken and then the volume of residual obturation material was calculated. Results: The residual obturation material was spotted in all samples. The mean percentage of residual obturation material was significantly lower when canals retreated with the R25/ Reciproc Blue file, while no significant differences were observed among the other three systems. A significant difference was noticed between GuttaCore and single-cone remnants of obturation material. Conclusion: Under the circumstances of the current study, the use of the Reciproc Blue system is more effective in removing root canal obturation material filled either with GuttaCore or single-cone obturation techniques. R, WO, and WOG systems resembled in the removal of obturation material. The removal of obturation materials from severely curved root canals obturated with GuttaCore is more difficult than the single cone